Antibodies from the Sera of Multiple Sclerosis Patients Efficiently Hydrolyze Five Histones - Baranova, Svetlana V. (Biomolecules, 2019)
It is known that intranuclear histones can be pernicious after entering to the extracellular space. In addition, the immunization of animals with exogenous histones leads to systemic inflammatory and toxic reactions. Abzymes—autoantibodies with enzymatic activities—are the distinctive feature of autoimmune diseases and they can be especially dangerous to humans. Here, electrophoretically homogeneous IgGs were isolated from sera of patients with multiple sclerosis (MS) by chromatography on several affinity sorbents. We present evidence that sera of all MS patients contain autoantibodies against histones and 73% of IgGs purified from the sera of 59 MS patients efficiently hydrolyze from one to five histones: H1, H2a, H2b, H3, and H4. The relative average efficiency of the histones hydrolysis was ~3.9-fold higher than that for healthy donors. The relative average activity of IgGs depends on the type of MS and decreased approximately in the following order: debut of MS, secondary progressive multiple sclerosis, remitting multiple sclerosis, remittent progressive multiple sclerosis. Similar to proteolytic abzymes of patients with several autoimmune diseases, histone-hydrolyzing IgGs from MS patients were inhibited in the presence of specific inhibitors of serine and of metal-dependent proteases, but an unexpected significant inhibition of the activity by inhibitors of thiol-like and especially acidic proteases was observed. Since IgGs can efficiently hydrolyze histones, a negative role of abzymes in the development of MS cannot be excluded.